2012
DOI: 10.1055/s-0032-1301887
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Exercise Affects Diurnal Variation of Some Biological Markers in Trained Subjects

Abstract: The study investigated if markers of muscle injury and antioxidant status were affected by a Wingate test performed at 2 different times of day. 15 young male footballers performed 2 tests (randomized) at 07:00-h and 17:00-h. Fasting blood samples were collected before and 3 min after each test for assessment of markers of muscle injury and antioxidant status. Resting oral temperature was recorded during each session. Peak power (10.76 ± 1.05 vs. 11.15 ± 0.83 W.kg( - 1)) and fatigue index (0.41 ± 0.04 vs. 0.49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 31 publications
(25 reference statements)
9
56
1
Order By: Relevance
“…In addition, it has also been suggested that increases in total bilirubin (TBIL) and uric acid (UA) levels are thought to reflect the imbalances in protein metabolic homeostasis and increased protein catabolism associated with tissue damage (i.e., CK and LDH increases) (32). Moreover, the previous studies have confirmed that there is a causal link between the diurnal variation of resting WBC, CK, and LDH and the circadian rhythm of core temperature in soccer players (16). From the evidence of similarity in the time of peak between temperature, muscle damage, and MDA levels (20), Kanabrocki et al (22) demonstrated a correlation between increased oxidative damage and increased rate of anabolic-catabolic events (e.g., oral temperature).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, it has also been suggested that increases in total bilirubin (TBIL) and uric acid (UA) levels are thought to reflect the imbalances in protein metabolic homeostasis and increased protein catabolism associated with tissue damage (i.e., CK and LDH increases) (32). Moreover, the previous studies have confirmed that there is a causal link between the diurnal variation of resting WBC, CK, and LDH and the circadian rhythm of core temperature in soccer players (16). From the evidence of similarity in the time of peak between temperature, muscle damage, and MDA levels (20), Kanabrocki et al (22) demonstrated a correlation between increased oxidative damage and increased rate of anabolic-catabolic events (e.g., oral temperature).…”
Section: Introductionmentioning
confidence: 86%
“…1). Olympic exercises and training hours were chosen according to the peak and the minimum of circadian rhythm of anaerobic performances and with regard to the findings reported in the literature (2,3,16).…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations